Risks associated with wastewater reuse in agriculture: investigating the effects of contaminants in soil, plants, and insects - Trotta, Vincenzo; Baaloudj, Oussama; Brienza, Monica (Frontiers in Environmental Science, 2024)
Rapid urbanization has heightened the urgency of the necessity for sustainable water management in agriculture. This review focuses on the impacts of using reused wastewater in agricultural practices, specifically highlighting the nutrient benefits and consequences of pollutants on important environmental elements. It investigates the impact of contaminants on agricultural ecosystems by assessing the soil composition and nutrient equilibrium. This research also examines the impact of pollution exposure on plants and insects, elucidating the behavioural adaptations and their broader ecological consequences in agricultural environments. Eventually, a comprehensive analysis was conducted to consolidate these findings, emphasizing the challenges and significance of implementing sustainable practices.This study highlights the necessity of addressing the health and environmental concerns associated with the agricultural reuse of wastewater, while also giving valuable information to guide future regulations.